2000
DOI: 10.1136/heart.83.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker lead related tricuspid stenosis: a report of two cases

Abstract: Only four cases of tricuspid stenosis related to endocardial pacemaker leads have been reported. Two further cases associated with perforation of a tricuspid valve leaflet by a pacemaker lead are presented: a 46 year old woman and a 60 year old man. It is possible that tricuspid valve disease related to endocardial pacemaker and non-thoracotomy defibrillator leads is underrecognised. Diagnosis requires clinical suspicion and the use of Doppler echocardiography. Recent evidence of fibrosis aVecting the tricuspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…One pilot study (18) showed improved symptoms and ventricular function when biventricular pacing was instituted in patients with presumed RV pacing-induced LV failure. In addition, case reports suggest that rightsided pacemaker wires may entrap or perforate the tricuspid valve, presenting with severe insufficiency (or even stenosis) and isolated RHF (19,20). Tricuspid insufficiency may also occur following RV biopsy, presumably as a result of damage to the chordae and loss of tricuspid valve coaptation (21).…”
Section: What Is It?mentioning
confidence: 99%
“…One pilot study (18) showed improved symptoms and ventricular function when biventricular pacing was instituted in patients with presumed RV pacing-induced LV failure. In addition, case reports suggest that rightsided pacemaker wires may entrap or perforate the tricuspid valve, presenting with severe insufficiency (or even stenosis) and isolated RHF (19,20). Tricuspid insufficiency may also occur following RV biopsy, presumably as a result of damage to the chordae and loss of tricuspid valve coaptation (21).…”
Section: What Is It?mentioning
confidence: 99%
“…In humans, endothelial injury, fibrosis, calcification and adhesions leading to tricuspid valve stenosis has also been described as a complication of looped transvenous leads. 6,7 In addition, multiple pacemaker leads, abandoned leads and large leads relative to vessel diameter have been linked to vascular wall inflammation, fibrosis and thrombosis caused by mechanical stress on the venous wall. 8,9 Similar vascular pathology resulting in obstruction to cranial vena cava blood flow has recently been reported secondary to the presence of dual chamber pacemaker leads in two dogs.…”
Section: Discussionmentioning
confidence: 99%
“…TS is almost always rheumatic in origin 1 and is usually associated with MS. Isolated TS can be seen with carcinoid syndrome, endocardial fibroelastosis, endomyocardial fibrosis, congenital tricuspid atresia, and systemic lupus erythematosus. Rarely, hemodynamic effects of obstruction to right ventricular inflow—like right atrial tumors, 2 large thrombi in the right atrium, a large vegetation, or pacemaker lead 3 —can mimic TS. Rheumatic TS is rare and is usually associated with MS with or without AS 4 .…”
Section: Discussionmentioning
confidence: 99%